Demokrasi Terganggu: Biaya Politik Tinggi, Politik Transaksional, dan Korupsi - Satriawan, Bismar Harris; Angela, Vivi Friskila (Ministry of Home Affairs, 2024)
High political costs have had implications for the degradation of democratic values ??which has caused democratic disruption to occur. This research aims to see the disruption of democracy in Indonesia that occurs in the phenomenon of high political costs, and how possible solutions can be offered. This research used a qualitative approach, with the library research method. The research results show that high political costs are the beginning of a transactional political and corruption phenomenon occurs. High political costs result in figures/candidates using various illegal methods to find sources of financing to fulfill political costs. High political costs and a process based on the logic of the power of financial, tends to open space for the birth of figures/candidates who are far from the values ??of integrity and quality through their ideas/performance. As an important momentum towards a future era of democracy that is more substantive, quality and dignified, several solutions that can be offered, namely: (1) Political parties and the government encourage the optimization of legal sources of political party funding assistance, both in cash and for future considerations through non-cash (in-kind) options, by providing strengthening aspects of accountability and transparency; (2) the government and election organizers strengthen the enforcement of regulations, supervision and strict sanctions, in political party funding; (3) political parties encourage the presence of figures/candidates who have integrity and quality values ??through their ideas/performance; (4) the government and election organizers can consider implementing digital democracy through e-voting in future elections in Indonesia.